Analisis Implementasi Aplikasi IFS (Industrial & Financial System) Dalam Prosedur Pembuatan Dokumen Bukti Pengeluaran Kas Dan Bank (O-15) Di PT Pal Indonesia - Arabela Fidelia Masnal Pabadakayo; Astrini Aning Widoretno (JURNAL ILMIAH NUSANTARA, 2024)
This study aims to determine whether the implementation of the IFS application in the procedure for making proof of cash and bank expenditure documents (O-15) is in accordance with the internal control of cash expenditure accounting information system procedures. The author uses a qualitative research method for this research, with data expressed descriptively. The data collection method is done through interviews and observations. This research was conducted directly at PT PAL Indonesia to collect primary data as part of field research. The results showed that the implementation of the IFS application in the procedure for making proof of cash and bank expenditure documents (O-15) of PT PAL Indonesia has been implemented properly.